¿Has the undergraduate student had changes in the distance – virtual modality? - Acuña Barrantes, Henry (2025)
This research aims to compare some variables with students enrolled in a Higher Education Institution (IES) pursuing distance-virtual undergraduate programs. The sample included students from the Faculty of Distance Studies (FAEDIS) at the Universidad Militar Nueva Granada (UMNG). A parallel was drawn between the 2015-II and 2024-I periods, comparing economic, demographic, and institutional aspects. A descriptive methodology was used, using a survey instrument that corresponded to a sample of 15.2% of the enrolled student body. The above shows that a significant proportion of the students who responded were between 22 and 35 years old, indicating a young adult population. However, the 17-21 age group showed a significant increase. Likewise, a representative percentage is seen in the variable "Scholarship from a third party" (46.0%), which can be awarded with the current national government aid through the Free Tuition Policy, better known as zero tuition.